BIBLIOMETRIC INSIGHTS INTO RESEARCH TRENDS AND COLLABORATIVE EFFORTS IN CREATIVITY AND CRITICAL THINKING IN HIGHER EDUCATION - Perdana, Yoga; Suryana, Suryana; Mulyadi, Hari; Askolani, Askolani (JURNAL APARATUR, 2024)
This study examines the role of creativity and critical thinking in higher education through bibliometric analysis, aiming to identify trends and gaps in the literature. Analyzing 588 documents from 2020 to 2023, key themes such as student engagement, instructional design, and sustainable development were identified. The findings underscore sustained research interest in higher education, creativity, and critical thinking, with a growing focus on creativity-related topics in recent years. Collaboration among authors and international partnerships was notable, highlighting the importance of cross-border knowledge exchange in addressing global challenges. The study emphasizes the need for innovative teaching methods and curriculum design to foster creativity and critical thinking effectively, informing strategies to enhance educational quality and prepare students for the demands of the 21st century.  ABSTRAK Penelitian ini mengkaji peran kreativitas dan pemikiran kritis dalam pendidikan tinggi melalui analisis bibliometrik, dengan tujuan untuk mengidentifikasi tren dan kesenjangan dalam literatur. Dengan menganalisis 588 dokumen dari tahun 2020 hingga 2023, tematik utama seperti keterlibatan siswa, desain pembelajaran, dan pembangunan berkelanjutan diidentifikasi. Temuan menunjukkan minat penelitian yang berkelanjutan dalam pendidikan tinggi, kreativitas, dan pemikiran kritis, dengan peningkatan fokus pada topik terkait kreativitas dalam beberapa tahun terakhir. Kolaborasi antara penulis dan kemitraan internasional sangat mencolok, yang menunjukkan pentingnya pertukaran pengetahuan lintas-batas dalam mengatasi tantangan global. Studi ini menekankan perlunya metode pengajaran dan desain kurikulum yang inovatif untuk mengembangkan kreativitas dan pemikiran kritis secara efektif, yang akan membantu dalam meningkatkan kualitas pendidikan dan mempersiapkan siswa menghadapi tantangan abad ke-21.